2021
DOI: 10.1159/000518220
|View full text |Cite
|
Sign up to set email alerts
|

Pruritus, Pain, and Depression Associated with the Most Common Skin Diseases: Data from the French Study “Objectifs Peau”

Abstract: <b><i>Background:</i></b> The prevalence and impact of pruritus, pain, and other sensory symptoms in skin diseases are poorly known. <b><i>Objective:</i></b> To assess the frequency of these symptoms with dermatoses and their association with depression using data from the “Objectifs Peau” survey. <b><i>Methods:</i></b> A representative sample of 20,012 French individuals was created using the usual quota method. <b><i>Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, due to the fact that both rosacea and BCC share the same risk factors -UV exposure, the potential association should not be neglected. According to recent studies, BCC may cause also itching of the skin [15], a symptom which was previously linked mostly to inflammatory skin conditions, such as rosacea [16]. What is worth noticing, most of the BCC in men in our group were located on the nose, which is also a typical location of rhinophyma.…”
Section: Discussionmentioning
confidence: 57%
“…However, due to the fact that both rosacea and BCC share the same risk factors -UV exposure, the potential association should not be neglected. According to recent studies, BCC may cause also itching of the skin [15], a symptom which was previously linked mostly to inflammatory skin conditions, such as rosacea [16]. What is worth noticing, most of the BCC in men in our group were located on the nose, which is also a typical location of rhinophyma.…”
Section: Discussionmentioning
confidence: 57%
“…Skin dryness and itching in patients with cervical cancer is mainly caused by inflammatory skin reactions caused by radiation exposure, which not only leads to changes in physical appearance and lowers patients’ self-esteem levels, but also significantly reduces patients’ quality of life and causes significant psychological burden ( Chu et al, 2021 ; Asada et al, 2022 ), with studies reporting insomnia in over 88% of patients with pruritic skin. Pruritic skin can significantly reduce patients’ quality of life, and with pruritic skin disease, patients are 1.4 times more likely to suffer from depressive mood or anxiety than those who do not ( Kopyciok et al, 2016 ; Huet et al, 2022 ). Therefore, taking into account the cost of intervention and patient benefit, it is recommended that in clinical psycho-oncology practice, the target of depression interventions when skin dryness and itching are present should be determined based on the specific quality of life and marital relations status of the cervical cancer patient.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study of 371 Chinese acne patients showed that itching was present in 45% of males and 46% of females [ 16 ]. Additionally, Huet et al [ 18 ] found itching in 48.55% of patients with acne. A higher frequency of itching was reported by Lim et al [ 15 ], who studied 120 acne patients with a mean age of 22 years (age range: 12–40 years), and demonstrated that 70% of the patients reported itching in acne lesions either at the time of study performance or in the past.…”
Section: Discussionmentioning
confidence: 99%
“…For years, acne has been regarded as a non-itchy skin condition. To the best of our knowledge, there are only a few reports on itching in acne patients available in the literature, indicating that at least some acne patients may experience itching sensations [ 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%